The annotated Alice - Carroll, Lewis, 1832-1898.; Carroll, Lewis, 1832-1898. Through the looking-glass. 1989.; Tenniel, John, Sir, 1820-1914; Gardner, Martin, 1914- (C.N. Potter : New York ; Distributed by Crown Publishers, 1989)
Presents both of Carroll's famous Alice stories, augmented by a recently discovered chapter,'Wasp in a Wig.' Includes commentary on the jokes, word games, mysteries, puzzles, riddles, parodies, and obscure references that Carroll interwove into his stories.
8902
Includes index.
Bibliography: p.